Повышение точности процесса автоматизации контроля параметров электронных компонент - Слипченко, Н. И.; Федотов, П. Д.; Федотов, Д. А. (ХНУРЭ, 2010)
Создание средств автоматизации контроля параметров электронных компонент и, в частности, полупроводниковых структур для солнечной энергетики является актуальной задачей. Creation of means for automation of control over electronic components’ parameters includes analogue signals conversion into the digital form. The available ADC capacity of the modern controllers provides the signal resolution of the order of 10-9, whereas the potentially accessible error of classical analogue devices does not exceed the value of 10-6. To eliminate such a discrepancy the authors investigated a number of circuits engineering solutions, specifically, attacking methods and means ensuring rise in the parameters precision.
Keywords: двухкаскадный усилитель; повторитель напряжения